2021
DOI: 10.1088/1361-648x/ac2bc7
|View full text |Cite
|
Sign up to set email alerts
|

Electron–phonon superconductivity in C-doped topological nodal-line semimetal Zr5Pt3: a muon spin rotation and relaxation (μSR) study

Abstract: In the present work, we demonstrate that C-doped Zr5Pt3 is an electron–phonon superconductor (with critical temperature T C = 3.8 K) with a nonsymmorphic topological Dirac nodal-line semimetal state, which we report here for the first time. The superconducting properties of Zr5Pt3C0.5 have been investigated by means of magnetization, resistivity, specific heat, and muon spin rotation and relaxation (μSR) measurements. We find that at low temperatures, the depolarization rate is almost constan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 83 publications
1
13
0
Order By: Relevance
“…However, recent muon-spin rotation and relaxation (μSR) results are consistent with a conventional s-wave pairing in Zr 5 Pt 3 C 0.5 [20]. More intriguingly, theoretical calculations predict that Zr 5 Pt 3 C x to be Dirac nodal-line semimetals and, as such, good candidates for realizing topological SC [20].…”
Section: Introductionmentioning
confidence: 80%
See 2 more Smart Citations
“…However, recent muon-spin rotation and relaxation (μSR) results are consistent with a conventional s-wave pairing in Zr 5 Pt 3 C 0.5 [20]. More intriguingly, theoretical calculations predict that Zr 5 Pt 3 C x to be Dirac nodal-line semimetals and, as such, good candidates for realizing topological SC [20].…”
Section: Introductionmentioning
confidence: 80%
“…In carbon-intercalated Zr 5 Pt 3 C x , the T c value depends nonmonotonically on x, first increasing up to 7 K for x = 0.3, then decreasing to ∼4 K as the amount of intercalated C is further increased [16,20]. The first electronic specific-heat and magnetic penetration-depth studies suggested that Zr 5 Pt 3 and Zr 5 Pt 3 C 0.3 are nodal superconductors, implying their unconventional SC character [16].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The presence of a flux-line lattice in the superconducting state results in an inhomogeneous field distribution within the sample, which in turn induces a faster decay in the asymmetry spectra below T C . The time evolution of the TF-µSR data at all temperatures above and below T C is best described by a sinusoidal oscillatory function damped with a Gaussian relaxation arising from muons implanted in the sample and an oscillatory background term from muons in the silver sample holder that do not depolarize [39][40][41][42]:…”
Section: B Superconducting Gap Structurementioning
confidence: 99%
“…The presence of a flux-line lattice in the superconducting state results in an inhomogeneous field distribution within the sample, which in turn induces a faster decay in the asymmetry spectra below T C . The time evolution of the TF-μSR data at all temperatures above and below T C is best described by a sinusoidal oscillatory function damped with a Gaussian relaxation arising from muons implanted in the sample and an oscillatory background term from muons in the silver sample holder that do not depolarize [39][40][41][42]:…”
Section: B Superconducting Gap Structurementioning
confidence: 99%